Effective Communication between Ustadz and Santri in Overcoming Bullying Cases in the Darul Ulum Ad-Diniyah Islamic Boarding School - Rokibullah Rokibullah (Advances In Social Humanities Research, 2026)
Bullying has become a critical issue in educational institutions, including Islamic boarding schools (pesantren), where it undermines students’ psychological well-being and contradicts the moral values upheld by these institutions. This study aims to examine the role of effective communication between ustadz (Islamic teachers) and santri (students) in addressing bullying cases at Darul Ulum Ad-Diniyah Islamic Boarding School. The research employs a qualitative case study approach to gain an in-depth understanding of communication practices within the pesantren context. Data were collected through participatory observation, in-depth interviews, documentation, and focus group discussions involving ustadz, students, and school administrators. The findings reveal that ustadz play a strategic role as role models, moral educators, and mediators in conflict resolution. Effective communication strategies such as two-way communication, empathetic interaction, the integration of religious values, and the use of group discussion forums (halaqah) significantly contribute to resolving bullying cases. These approaches not only encourage perpetrators to recognize and change their behavior but also help victims rebuild self-confidence and feel supported. Furthermore, effective communication fosters a harmonious and conducive environment within the pesantren, strengthening social bonds and promoting Islamic values of brotherhood. This study highlights that communication grounded in empathy, openness, and religious principles serves as an effective tool for social transformation and conflict resolution in Islamic boarding schools.